O’CONNOR, Kathleen M. Jeremiah Pain and Promise. Minneapolis, MN: Fortress, 2011. 179 p. - Yan, Anderson (Vox Scripturae - Revista Teológica Internacional, 2014)
O’CONNOR, Kathleen M. Jeremiah Pain and Promise. Minneapolis, MN: Fortress, 2011. 179 p.